Description Of The Mistakes Of The Fifth Graders Of SD Negeri 1502 Pioner Siborna In Solving Math Problems - Siti Ayuna Nasution (Indonesian Journal of Basic Education, 2022)
The purpose of this study was to find out what mistakes were made by the students of SD Negeri 1502 Pioner Siborna in grade 5 odd questions when solving math problems. The method used in this research is qualitative and descriptive type of research. The subjects of this study were all fifth grade students of SD Negeri 1502 Pioner Siborna, totaling 26 students consisting of 16 female students and 10 male students. The data collection technique used in this research is the use of documents and interviews. The purpose of this documentation is to find out the mistakes students made with their math problems in Semester 2. The purpose of the interviews was to obtain information about alternative answer choices and to analyze students' errors in the questions given. Based on the data analysis of the results of this study, it can be concluded that students make more conceptual errors than errors caused by principles, operations, and carelessness. Conclusions based on the results of data analysis are the conceptual error rate is 35.54%, the principle error rate is 31.24%, the operating error rate is 21.95%, and the careless error rate is 11.27%